Application of Gene Structure and Mitosis Concepts to the Study and Design of Folding Mechanisms. (January 2015) - Yang, Fei; Deng, Zongquan; Tao, Jianguo; Jiang, Shengyuan; Yue, Honghao
The goal of this study was to develop a novel approach to the study and design of metamorphic mechanisms, based on a consideration of gene structure, mitosis, and cell fusion. In this study, we treat kinematic pairs as basic connection units that function similarly to the base pairs in DNA molecules and present expressions for the configuration of each kinematic pair in a mechanism. We also develop some methods to describe changes in the number of links, number of kinematic pairs, and pair features (type and configuration) during the folding process. Finally, we propose a method based on mitosis and cell fusion for studying the folding process and innovating mechanism design. In this method, a mechanism is first decomposed into some basic kinematic chains, and then these chains (with folding function) are fused into one complete mechanism. Two examples are presented to demonstrate the use of the methods proposed in this study. Overall, we found that, for innovation in mechanism design, it is useful to consider gene connection and mutation as well as mitosis and cell fusion.